Pardeh-khani a conceptual model for Iranian national cinema / Majid Fadaei - Fadaei, Majid (2014)

(untitled)
This research has proposed Iran’s traditional art of Pardeh-khani as a suitable and applicable model for attaining a national cinema in this country; Pardeh-khani (pictorial storytelling) or Parde-dari is a kind of storytelling and minstrelsy with painted canvases that some scenes of epic, myth, moral and especially religious stories are painted on them. Mixture of speech and image in Pardeh-khani cause this kind of storytelling in the most popular and dramatic kind within Iran ancient arts. Pardeh-khani is very similar to modern art of cinema which served an analogous function in the past. Iran’s cinema, despite producing decorated works and eye-catching successes in global festivals during its 110-years history (1900-2010), has not been able yet to gain its actual position and status. It has failed to become a national cinema having a unique identity. As a matter of fact, despite all cultural and artistic potentials and capabilities of ancient Iran’s civilization and also presence of creative artists, Iran’s cinema has not managed to possess a national style with an identity commensurate with culture and identity of this civilization. By investigating different dimensions of this art that enjoyed remarkable popularity among Iranians along the history until a near past, this study attempts to render a theoretical and practical framework for national cinema in Iran.